PEMANFAATAN E-LEARNING DAN MEDIA SOSIAL DALAM PEMBELAJARAN BAHASA DAN SASTRA INDONESIA - Ricky Saputra; Yulida; Rezki Muhammad Akbar; Reni Kusmiarti (Universitas Muhammadiyah Bengkulu, 2026)
The rapid development of information and communication technology has significantly transformed the field of education, including Indonesian language and literature learning. The utilization of digital technologies such as e-learning and social media provides opportunities for teachers and students to create more interactive, flexible, and collaborative learning environments. This article aims to describe the use of e-learning and social media in Indonesian language and literature learning and to analyze their impact on student engagement and motivation. This study employs a qualitative descriptive approach using a literature review method. Data were collected from various academic sources including national and international journals, academic books, and research reports related to digital learning. The findings indicate that the use of e-learning and social media can increase student participation, broaden access to learning resources, and support the development of digital literacy. Platforms such as Google Classroom, WhatsApp, YouTube, and Instagram can function as media for distributing learning materials, facilitating discussions, publishing students’ works, and encouraging collaborative learning. However, proper management and teacher supervision are required to ensure that technology use remains aligned with educational goals. Therefore, the integration of e-learning and social media can serve as an innovative strategy to enhance the quality of Indonesian language and literature learning in the digital era. Keywords: e-learning, social media, Indonesian language learning Abstrak Perkembangan teknologi informasi dan komunikasi telah membawa perubahan signifikan dalam dunia pendidikan, termasuk dalam pembelajaran Bahasa dan Sastra Indonesia. Pemanfaatan teknologi digital seperti e-learning dan media sosial memberikan peluang bagi guru dan siswa untuk menciptakan proses pembelajaran yang lebih interaktif, fleksibel, dan kolaboratif. Artikel ini bertujuan untuk mendeskripsikan pemanfaatan e-learning dan media sosial dalam pembelajaran Bahasa dan Sastra Indonesia serta mengkaji dampaknya terhadap motivasi dan keterlibatan belajar siswa. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan metode studi pustaka. Data diperoleh dari berbagai sumber literatur ilmiah berupa jurnal nasional dan internasional, buku akademik, serta laporan penelitian terkait pembelajaran digital. Hasil kajian menunjukkan bahwa pemanfaatan e-learning dan media sosial mampu meningkatkan partisipasi siswa, memperluas akses terhadap materi pembelajaran, serta mendukung pengembangan literasi digital. Platform seperti Google Classroom, WhatsApp, YouTube, dan Instagram dapat dimanfaatkan sebagai media distribusi materi, diskusi, publikasi karya siswa, serta sarana kolaborasi pembelajaran. Namun demikian, penggunaan teknologi digital juga memerlukan pengelolaan yang baik agar tidak menimbulkan distraksi dan tetap berorientasi pada tujuan pembelajaran. Dengan demikian, integrasi e-learning dan media sosial dapat menjadi strategi inovatif dalam meningkatkan kualitas pembelajaran Bahasa dan Sastra Indonesia di era digital.